Faktor Makro Ekonomi Yang Mempengaruhi Pergerakan Harga Saham Pada Indeks Saham Syariah Indonesia (ISSI) di Bursa Efek Indonesia (BEI) - Rachmawati, Martien; Laila, Nisful (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The capital market presence is such an important concern for many country because itÂ relate to its function as economic booster through investation. This study aims to analyzeÂ macro economic factors that can affect the movement of stock price at Indonesia ShariaÂ Stock Index in Indonesia Stock Exchange as the inflation factor, SBI interest rates andÂ exchange rates. The method used in this research is quantitative approaches in which data isÂ obtained from Indonesia Stock Exchange and Bank of Indonesia. The data used is the timeÂ series data starting from January 2012 to April 2015. The statistical tool used is multiple linearÂ regression. Result showed that partially inflation is not significant and have a negative relationÂ toward ISSIâs stock price, SBI interest rate is not significant and have a positive relation towardÂ ISSIâs stock price, exchange rate significantly influence the stock price at Indonesia ShariaÂ Stock Index (ISSI) and have a negative effect. Simultaneously, both variable inflation rate, SBIinterest rate and the exchange rate significantly influence the stock priceâs movement atÂ Indonesia Sharia Stock Index (ISSI).